2008
DOI: 10.2116/analsci.24.1355
|View full text |Cite
|
Sign up to set email alerts
|

Simplex-optimized Chromatographic Resolution of Selected Ionic Liquid Cations Utilizing a Polar Reversed-Phase System

Abstract: This study reports on optimization of the RP-HPLC separation of imidazolium and pyridinium ionic liquid cations using a variable-size simplex algorithm. Under the optimized conditions, all critical pairs of ionic liquids were successfully separated in a single chromatographic run. The mobile phase at the point corresponding to the optimum consisted of 10% MeOH and 90% 15 mM KH2PO4/H3PO4 with pH 3.43. The coefficients of asymmetry for all of the compounds analyzed at the simplex algorithm optimum ranged from 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…The LODs and LOQs of the 23 ILs in the soil samples were in the range of 0.15-2.88 ng g À1 and 0.50-9.50 ng g À1 , respectively. Compared to the previous studies, the LODs achieved in the present method were lower than those of conventional IC, 24-27 HPLC, 28,29,34,45 and CE. 38,39 These results indicated that the present method was an efficient and sensitive method for the determination of trace amounts of ILs.…”
Section: Methods Validationcontrasting
confidence: 75%
See 2 more Smart Citations
“…The LODs and LOQs of the 23 ILs in the soil samples were in the range of 0.15-2.88 ng g À1 and 0.50-9.50 ng g À1 , respectively. Compared to the previous studies, the LODs achieved in the present method were lower than those of conventional IC, 24-27 HPLC, 28,29,34,45 and CE. 38,39 These results indicated that the present method was an efficient and sensitive method for the determination of trace amounts of ILs.…”
Section: Methods Validationcontrasting
confidence: 75%
“…To date, many methods have been developed for IL cation determination, such as ion chromatography (IC), [24][25][26][27] ion-pair chromatography (IPC), 28,29 reversed phase liquid chromatography (RPLC), [30][31][32][33][34] hydrophilic interaction liquid chromatography (HILIC), 35,36 ultra-performance liquid chromatography (UPLC), 37 capillary electrophoresis (CE), 38,39 and capillary isotachophoresis (CITP). 40 Among them, Stepnowski's group has carried out extensive work, and developed a number of analytical methods for the determination of IL cations and anions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mobile phases consisted of organic modifiers, aqueous solutions modified with ion pair reagents or different buffer systems, the compositions of which were optimized using the simplex algorithm. [3][4][5] Additionally, various stationary phases, mainly those of increased polarity, were tested with the aim of improving the selectivity and specificity of the analytical methods. [6][7][8] Furthermore, capillary electrophoresis for resolving selected imidazolium cations was reported as an additional method for analysing IL cations.…”
Section: Introductionmentioning
confidence: 99%